Analysis of Zakat Management with Institutional Isomorphic Theorizing Approach - Mufti Afif; Ahmad Agus Hidayat; Ahmad Suminto; Taufiqul Alvin Abidin; Fahmi Akhyar Al Farabi (Universitas Pembangunan Nasional Veteran Jakarta, 2023)
The potential of zakat in East Java is significant, reaching Rp547.4 billion. However, the collection results of ZIS by Baznas of East Java, both collected by Baznas at the provincial level and in districts/cities in East Java in 2021, only reached Rp122 billion. This means that only about 25 percent of ZIS potential could be collected. The objective of this study is to investigate how zakat institution applies institutional isomorphic theory to governance and administration. The research was conducted in Laznas Yatim Mandiri Ponorogo that employed in-depth interviews, observations, and documentation. Meanwhile, data sources were drawn from various references including journals, books, and other articles. The findings of the study demonstrate that the Laznas Yatim Mandiri in Ponorogo, Indonesia has managed in a coercive manner, within compliance with the shariah law and the 1945 Constitution. Through mimetic features, the Laznas Yatim Mandiri's administration has embraced many of the governance practices of other charitable institutions, particularly in the areas of information collecting, distribution, and transparency. In addition, the administration of the Laznas Yatim Mandiri through the normative aspect has served its purpose as an institution that adheres to the principles of good corporate governance, which include transparency, accountability, responsibility, independence, fairness, and equality. Potensi zakat di Jawa Timur cukup besar yakni mencapai Rp547,4 miliar. Namun hasil penghimpunan ZIS yang dilakukan Baznas Jatim, baik yang dihimpun Baznas tingkat provinsi maupun kabupaten/kota di Jatim pada tahun 2021, hanya mencapai Rp122 miliar. Artinya, potensi ZIS yang bisa dihimpun baru sekitar 25 persen. Tujuan dari penelitian ini adalah untuk menyelidiki bagaimana lembaga zakat menerapkan teori isomorfik kelembagaan dalam tata kelola dan administrasi. Penelitian dilakukan di Laznas Yatim Mandiri Ponorogo dengan menggunakan wawancara mendalam, observasi, dan dokumentasi. Sedangkan sumber data diambil dari berbagai referensi antara lain jurnal, buku, dan artikel lainnya. Temuan penelitian menunjukkan bahwa Lembaga Zakat Yatim Mandiri di Ponorogo, Indonesia telah melakukan pengelolaan secara korosif, sesuai dengan hukum syariah dan UUD 1945. Melalui ciri-ciri mimesis, penyelenggaraan Lembaga Zakat Yatim Mandiri telah banyak mengadopsi praktik tata kelola lembaga amal lainnya, khususnya di bidang pengumpulan, distribusi, dan transparansi informasi. Selain itu, penyelenggaraan Lembaga Zakat Yatim Mandiri melalui aspek normatif telah mencapai tujuannya sebagai lembaga yang berpegang teguh pada prinsip-prinsip tata kelola perusahaan yang baik yang meliputi transparansi, akuntabilitas, tanggung jawab, independensi, kewajaran, dan kesetaraan.